Age and individual sleep characteristics affect cognitive performance among anaesthesiology residents after a 24-hour shift - Tadinac, Meri (Array, 2014)
Background: Previous research has shown that both shift work and sleep deprivation have an adverse influence on various aspects of human cognitive performance. The aim of this study was to explore changes in cognitive functioning and subjective sleepiness of anaesthesiology residents after a 24-hour shift Method: A total of 26 anaesthesiology residents completed a set of psychological instruments at the beginning and at the end of the shift, as well as a questionnaire regarding information about the shift, Stanford sleepiness scale, and Circadian type questionnaire. Results: There was a significant decline in cognitive performance measured by Auditory Verbal Learning Test (AVLT) after the shift. The effect was stronger in older participants, and those with high scores on rigidity of sleep scale and low scores on the ability to overcome sleepiness scale. There were no differences in the Digits forward test (a measure of concentration), while Digits backward test (a measure of working memory) even showed an improved performance after the shift. Although participants reported being significantly sleepier after the shift, the subjective sleepiness did not correlate with any of the objective measures of cognitive performance. Conclusions: The performance in short tasks involving concentration and working memory was not impaired, while performance in long-term and monotone tasks declined after sleep deprivation, and the magnitude of this decline depended on specific individual characteristics of sleep, and on age. Surprisingly, age seems to have an important impact on cognitive functions after shift work even in the relatively age-homogenous population of young anaesthesiology residents.